Polymorphisms of Palu Sheep IGF-1 Gene and Their Relationship with Skeletal Growth - Malewa, A. Dg.; Awaluddin, (Tropical Animal Science Journal, 2022)
This study aims to examine the polymorphisms of the IGF-1 gene associated with body weight and size. A total of 60 sheep from different farm locations in Palu City (Villages of Taipa, Poboya, Kawatuna, and Petobo), Central Sulawesi, Indonesia, were used. The variables observed were adult body weight and measurements, such as shoulder height, body length, humerus length, radius-ulna length, metacarpus length, hip height, femur length, tibial length, and metatarsus length as phenotypic characteristics. IGF-1 gene polymorphisms were analyzed using the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) with Bsp143ǀǀ as a restriction enzyme. These gene polymorphisms were calculated using the allele and genotype frequency approach, as well as the Polymorphic Informative Content (PIC). Genotype associations with body weight and bone size were analyzed using the General Linear Model analysis method. The PCR-RFLP analysis results showed the presence of polymorphisms with the frequency and genotypes of GG (21.7%), GC (68.3%), and CC (10%). Furthermore, the frequencies of G (55.8%) and C (44.2%) genes with a 49.32% polymorphism rate (PIC) were not in the Hardy-Weinberg equilibrium (p